The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/pcan.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prostate cancer association with four single-nucleotide polymorphisms from genome-wide studies and serum phyto-estrogen concentrations

Abstract: BACKGROUND: Both genetics and the environment are implicated as risk factors for prostate cancer (PCa). This populationbased case--control study evaluated four single-nucleotide polymorphisms (SNPs) previously identified by genome-wide association studies to be associated with increased PCa susceptibility. Potential relationships between serum concentrations of phyto-estrogens and SNPs were also investigated. METHODS: Four SNPs (rs10993994, rs2660753, rs1016343 and rs6983267) were genotyped in 247 PCa patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…However, our outcomes were different to the results shown by Ho et al . [ 73 ], which demonstrated that rs6983267 polymorphism was not associated with prostate cancer. This discrepancy may be caused by the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our outcomes were different to the results shown by Ho et al . [ 73 ], which demonstrated that rs6983267 polymorphism was not associated with prostate cancer. This discrepancy may be caused by the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Ho et al . [ 73 ] included only 521 subjects (247 cases and 274 controls), which may lack sufficient power to support or deny an association. Previous meta-analyses also focused on the relationship between the rs6983267 and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among these single nucleotide polymorphisms (SNPs), several genome-wide association studies (GWASs) identified rs10993994 polymorphism in the promoter region of MSMB gene [7, 8], which was significantly associated with PC susceptibility. Subsequent studies [918] also investigated the association between MSMB gene rs10993994 polymorphism and PC susceptibility, but with conflicting conclusions. These studies were conflicting and inconclusive probably due to different ethnic populations, clinical heterogeneity, and small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Till date, there have been 30 SNPs reported in the dbSNP ( http://www.ncbi.nlm.nih.gov/projects/SNP/snp_ref ) corresponding to the MSMB proximal promoter region of which rs10993994 is well established as a susceptibility locus for PCa. However, there are few reports which suggest that this SNP has not been found to be a predisposing factor for benign prostatic hyperplasia (BPH) development (Ho et al 2012 ; Ban and Yoo 2014 ). Further, the MSMB promoter region has recently been studied extensively; using in vitro analysis and a ~370 bp region has been shown to harbour the core promoter and two negative regulatory elements.…”
Section: Introductionmentioning
confidence: 99%